Comprehensive evaluation of MRCP versus ultra sonography in biliary obstruction - Kaur, Amarjit; Malaviya, Aniket; Deepika, Deepika; Kaur, Navkiran (International Journal of Medical Research and Review, 2018)
Background: Biliary disorders are one of the common problems routinely seen in clinical practice. Ultrasound (USG) is an initial investigation and Magnetic resonance cholangiopancreatography (MRCP) is a relatively new technique, which has gained popularity because of its excellent diagnostic capabilities in the evaluation of biliary obstruction. Aims: The aim of our study was to know the cause and grade of obstruction in case of clinically suspected biliary obstruction and to evaluate and correlate the accuracy between MRCP and Ultra sonography. Material and Methods: This prospective cross sectional comparative study was conducted in the department of Radiology, Government medical college and Rajindra hospital, Patiala. 50 patients with suspected biliary obstruction with clinical and laboratory features suggestive of obstructive jaundice who were referred for USG, followed by MRCP were studied. Results: Most common disorder observed was choledocholithiasis 16 (32%), followed by carcinoma gall bladder with 7 (14%) cases, periampullary carcinoma with 6 (12%) cases, cholangiocarcinoma and benign stricture with 5 (10%) cases each, carcinoma head of pancreas with 4 (8%) cases, postoperative stricture with 3 (6%) cases and choledochal cyst and cholangitis with 2 (4%) cases each. The overall sensitivity, specificity, positive predictive value and diagnostic accuracy of MRCP in diagnosing biliary obstructive disease was 98%, 100%, 100% and 100%respectively as compared to 60%, 100%, 100%and 97% of USG. Conclusion: Ultrasound is considered the primary screening investigation modality of choice However, owing to its low sensitivity in most of the benign stenosis and distal common bile duct disease, where the clinical and laboratory suspicion is strong, MRCP is highly accurate, non-invasive, sensitive, non-ionizing and superior diagnostic modality in establishing diagnosis of obstructive biliary pathologies.